Whole genome sequencing and analysis reveal insights into the genetic structure, diversity and evolutionary relatedness of luxI and luxR homologs in bacteria belonging to the Sphingomonadaceae family - Gan, Han Ming; Gan, Huan You; Ahmad, Nurul H.; Aziz, Nazrin A.; Hudson, André O.; Savka, Michael A. (Frontiers in Cellular and Infection Microbiology, 2015)
Here we report the draft genomes and annotation of four N-acyl homoserine lactone (AHL)-producing members from the family Sphingomonadacae. Comparative genomic analyses of 62 Sphingomonadacae genomes were performed to gain insights into the distribution of the canonical luxI/R-type quorum sensing network within this family. Forty genomes contained at least one luxR homolog while the genome of Sphingobium yanoikuyae B1 contained seven Open Reading Frames (ORFs) that have significant homology to that of luxR. Thirty-three genomes contained at least one luxI homolog while the genomes of Sphingobium sp. SYK6, Sphingobium japonicum and Sphingobium lactosutens contained four luxI. Using phylogenetic analysis, the sphingomonad LuxR homologs formed five distinct clades with two minor clades located near the plant associated bacteria LuxR solo clade. This work for the first time shows that thirteen Sphingobium and one Sphingomonas genome(s) contain three convergently oriented genes composed of two tandem luxR genes proximal to one luxI (luxR-luxR-luxI) which we term convergent double luxR, luxI group. Interestingly, luxI solos were identified in two Sphingobium species and may represent species that contribute to AHL-based quorum sensing system by contributing AHL molecules but are unable to perceive AHLs as signals. This work provides the most comprehensive description of the luxI/R circuitry and genome-based taxonomical description of the available sphingomonad genomes to date indicating that the presence of luxR solos and luxI solos are not an uncommon feature in members of the Sphingomonadaceae family.